Java distributed computing - Farley, Jim (O'Reilly, 1998)
"Java Distributed Computing discusses how to design and write distributed applications in Java. It covers Java's RMI (Remote Method Invocation) facility and CORBA, but it doesn't stop there; it tells you how to design your own protocols to build message-passing systems, discusses how to use Java's security facilities, how to write multithreaded servers, and more. It pays special attention to distributed data systems, collaboration, and applications that have high bandwidth requirements."--Jacket
Includes index. - Print version record
Keywords: Java (Computer program language); Electronic data processing -- Distributed processing; Java (Langage de programmation); Traitement réparti; COMPUTERS; Programming Languages; Java; Electronic data processing; Distributed processing; Java (programmeertaal); Computernetwerken